Polymer blends having improved thermal properties

By using a polymer mixture composed of 1% to 40% of the crystalline block composite and 60% to 99% of the partially neutralized precursor acid copolyester ionic polymer, the problems of easy deformation and optical properties of existing plastic packaging materials under high temperature conditions are solved, and the effects of improving load bending temperature, rigidity and modulus, upper limit usage temperature and long-term creep performance are achieved, while maintaining good optical properties.

JP7654639B2Active Publication Date: 2025-04-01DOW GLOBAL TECHNOLOGIES LLC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022512448
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-29
Filing Date
2020-08-27
Publication Date
2025-04-01
Estimated Expiration
2040-08-27

AI Technical Summary

Technical Problem

Existing plastic packaging materials are prone to deform, flow or creep under high temperature conditions, and their optical properties are affected during injection molding.

Method used

A polymer mixture consisting of 1% to 40% of the crystalline block complex and 60% to 99% of the partially neutralized precursor acid copolyester ionic polymer was used. The mixture includes EP-iPP double-resistance polymer, isomeristic propylene ester homopolymer and ethylene propylene copolymer and is formed by specific polymerization processes and addition polymerization conditions.

Benefits of technology

It improves load bending temperature, rigidity and modulus at room and high temperatures, upper limit usage temperature and high temperature long-term crep performance, while maintaining good optical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654639000001
    Figure 0007654639000001
  • Figure 0007654639000002
    Figure 0007654639000002
  • Figure 0007654639000003
    Figure 0007654639000003
Patent Text Reader

Abstract

Embodiments are directed to polymer blends and molded articles comprising the polymer blends. Polymer blend embodiments may include 1 to 40 wt. % crystalline block composite and 60 to 99 wt. % ionomer formed from a partially neutralized precursor acid copolymer. The crystalline block composite may include EP-iPP diblock polymer, isotactic polypropylene homopolymer, and ethylene and propylene copolymer. The crystalline block composite may include greater than 50 wt. % isotactic polypropylene homopolymer. The precursor acid copolymer may include copolymerized units of ethylene and 5 to 30 wt. % copolymerized units of an α,β-ethylenically unsaturated carboxylic acid having 3 to 8 carbon atoms, based on the total weight of the precursor acid copolymer. About 25 to about 65% of the acid groups derived from the α,β-ethylenically unsaturated carboxylic acid of the precursor acid copolymer may be neutralized.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 62 / 893,364, filed Aug. 29, 2019, the entire disclosure of which is incorporated herein by reference.

[0002] FIELD OF THE DISCLOSURE Embodiments of the present disclosure relate generally to polymer blends, and more specifically, to polymer blends for use in molded articles. [Background technology]

[0003] Glass may be often used in cosmetic packaging applications due to its scratch resistance, transparency, hardness, and chemical resistance. However, the use of glass may be relatively expensive, and in some cases may be too costly. For example, glass may be quite dense and heavy, and therefore transportation costs may be high. Glass may be quite resistant to surface scratches, but it is also brittle. Summary of the Invention

[0004] Plastic cosmetic packaging can overcome some of the shortcomings of glass packaging by using ionomers. However, because ionomers are thermoplastic, their use can be limited by the possibility of deformation, flow, or creep under high temperature operating conditions. For example, ionomers can be susceptible to deformation, flow, or creep during the injection molding process. In addition, containers produced by the injection molding process can often have thick wall structures. When ionomers are used to mold such injection molded containers, optical properties can be reduced due to the wall thickness.

[0005] Thus, a need exists for ionomer compositions that can have improved deflection temperature under load, improved stiffness and modulus (at room temperature and at elevated temperatures below the melting point of the ionomer), improved upper service temperature at a given stiffness, and improved long-term creep at elevated temperatures, all while maintaining desirable optical properties.

[0006] The presently disclosed embodiments meet these needs by providing polymer blends that may include 1-40 wt% of a crystalline block composite and 60 wt%-99 wt% of an ionomer formed from a partially neutralized precursor acid copolymer. Compared to comparative ionomer compositions and blends, the presently disclosed polymer blends may have improved deflection temperature under load, improved stiffness and modulus (at room temperature and at elevated temperatures below the melting point of the ionomer), improved upper temperature limits at a given stiffness, and improved long-term creep at elevated temperatures while maintaining desirable optical properties. In embodiments, the presently disclosed polymer blends may be injection molded to form articles. The article embodiments may be utilized in cosmetic packaging applications.

[0007] Embodiments are directed to polymer blends and molded articles comprising the polymer blends. The polymer blend embodiments may include 1-40 wt. % of a crystalline block composite and 60 wt. %-99 wt. % of an ionomer formed from a partially neutralized precursor acid copolymer. The crystalline block composite may include EP-iPP diblock polymer, isotactic polypropylene homopolymer, and copolymer of ethylene and propylene. The crystalline block composite may include greater than 50 wt. % of an isotactic polypropylene homopolymer. The precursor acid copolymer may include copolymerized units of ethylene and 5 wt. %-30 wt. % of copolymerized units of an α,β-ethylenically unsaturated carboxylic acid having 3-8 carbon atoms, based on the total weight of the precursor acid copolymer. About 25% to about 65% of the acid groups derived from the α,β-ethylenically unsaturated carboxylic acid of the precursor acid copolymer may be neutralized.

[0008] These and other embodiments are described in greater detail in the detailed description that follows. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Certain embodiments of the present application will now be described. These embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the claimed subject matter to those skilled in the art.

[0010] Unless stated to the contrary, implied from the context, or customary in the art, all parts and percentages are by weight, all temperatures are in degrees Celsius, and all test methods are current as of the filing date of this disclosure.

[0011] The term "polymer" refers to a polymeric compound prepared by polymerizing monomers, whether of the same or different types. Thus, the generic term polymer generally encompasses the term "homopolymer," which refers to a polymer prepared from only one type of monomer, as well as "copolymer," which refers to a polymer prepared from two or more different types of monomers. As used herein, the term "interpolymer" refers to a polymer prepared by polymerization of at least two different types of monomers. Thus, the generic term interpolymer includes copolymers, and polymers prepared from three or more different types of monomers, such as terpolymers.

[0012] "Polyethylene" or "ethylene-based polymer" shall mean a polymer containing more than 50 mole percent units derived from ethylene monomer. This includes ethylene-based homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of ethylene-based polymers known in the art include, but are not limited to, low density polyethylene (LDPE), linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), single-site catalyzed linear low density polyethylene (m-LLDPE) including both linear and substantially linear low density resins, medium density polyethylene (MDPE), and high density polyethylene (HDPE).

[0013] As used herein, the term "composition" refers to a mixture of materials that comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.

[0014] As used herein, the term "polypropylene" or "propylene-based polymer" refers to a polymer that contains, in polymerized form, more than 50 mole percent units derived from propylene monomers, including propylene homopolymer, random copolymer polypropylene, impact copolymer polypropylene, propylene / α-olefin copolymer, and propylene / α-olefin copolymer.

[0015] The terms "blend", "polymer blend" and the like refer to a composition of two or more polymers. Such blends may or may not be miscible. Such blends may or may not be phase separated. Such blends may or may not contain one or more domain configurations as determined from transmission electron spectroscopy, light scattering, X-ray scattering, and any other method known in the art. A blend is not a laminate, although one or more layers of a laminate may contain the blend. Such blends may be prepared as dry blends, formed in situ (e.g., in a reactor), as melt blends, or using other techniques known to those skilled in the art.

[0016] The term "crystalline" refers to a material that has a first order transition or crystalline melting point (T m ) refers to a polymer or polymer block having a crystallinity of 100 to 200 nm. This term may be used interchangeably with the term "semicrystalline."

[0017] The term "crystallizable" refers to a monomer that can be polymerized such that the resulting polymer is crystalline. Crystalline ethylene polymers typically have, but are not limited to, densities of 0.89 g / cc to 0.97 g / cc and melting points of 75°C to 140°C. Crystalline propylene polymers typically have, but are not limited to, densities of 0.88 g / cc to 0.91 g / cc and melting points of 100°C to 170°C.

[0018] The term "amorphous" refers to a polymer that lacks a crystalline melting point.

[0019] The term "isotactic" refers to polymer repeat units having at least 70 percent isotactic pentads as determined by 13C-NMR analysis. "Highly isotactic" is defined as a polymer having at least 90 percent isotactic pentads.

[0020] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of any doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless otherwise stated to the contrary. In contrast, the term "consisting essentially of" excludes from the scope of any succeeding description any other components, steps, or procedures, except those that are not essential to operability. The term "consisting of" excludes any components, steps, or procedures not specifically delineated or listed.

[0021] Polymer Blends Reference will now be made in detail to the embodiments of the polymer blends as further described herein. In embodiments, the polymer blends may include crystalline block composites and ionomers.

[0022] Embodiments of the polymer blend may include from about 1% to about 40% by weight of the crystalline block composite, based on the total weight of the polymer blend. In some embodiments, the polymer blend may include from about 1% to about 30% by weight, 1% to about 20% by weight, from about 1% to about 10% by weight, from about 1% to about 5% by weight, from about 5% to about 30% by weight, from about 5% to about 20% by weight, from about 5% to about 15% by weight, from about 5% to about 10% by weight, from about 10% to about 30% by weight, from about 10% to about 20% by weight, or from about 20% to about 30% by weight, based on the total weight of the polymer blend.

[0023] Embodiments of the polymer blend may include 60% to 99% by weight of the ionomer formed from the partially neutralized precursor acid copolymer, based on the total weight of the polymer blend. In some embodiments, the polymer blend may include about 60% to about 90% by weight, about 60% to about 80% by weight, about 60% to about 70% by weight, about 70% to about 99% by weight, about 70% to about 90% by weight, about 70% to about 80% by weight, about 80% to about 99% by weight, about 80% to about 90% by weight, about 85% to about 95% by weight, or about 90% to about 99% by weight of the ionomer, based on the total weight of the polymer blend.

[0024] Crystalline Block Complex Reference will now be made in detail to the crystalline block composite embodiments of the polymer blends described herein. The term "crystalline block composite" (CBC) refers to a polymer comprising an EP-iPP diblock polymer, iPP, and EP, where iPP may refer to an isotactic polypropylene homopolymer and EP may refer to a copolymer of ethylene and propylene.

[0025] In embodiments, the crystalline block composite may include more than 50 wt% isotactic polypropylene based on the total weight of the crystalline block composite. That is, the crystalline block composite may include more than 50 wt% or more than 60 wt% isotactic polypropylene based on the isotactic polypropylene contained in the EP-iPP diblock polymer and the isotactic polypropylene homopolymer of the crystalline block composite. In other embodiments, the crystalline block composite may include about 55 wt% to about 85 wt% or about 60 wt% to about 75 wt% isotactic polypropylene based on the total weight of the crystalline block composite. Without being bound by theory, it has been surprisingly discovered that the inclusion of more than 50 wt% isotactic polypropylene results in a product having an improved balance of heat deflection temperature, oven creep resistance, and optical performance (e.g., clarity).

[0026] In embodiments, the crystalline block composite can have a melt flow rate MFR (per ASTM D1238 at 230° C., 2.16 kg) of about 2 g / 10 min to about 50 g / 10 min. In some embodiments, the crystalline block composite may have a melt flow rate MFR (per ASTM D1238 at 230° C., 2.16 kg) of about 2 g / 10 min to about 25 g / 10 min, about 2 g / 10 min to about 10 g / 10 min, about 2 g / 10 min to about 5 g / 10 min, about 5 g / 10 min to about 50 g / 10 min, about 5 g / 10 min to about 25 g / 10 min, about 5 g / 10 min to about 10 g / 10 min, about 10 g / 10 min to about 50 g / 10 min, about 10 g / 10 min to about 25 g / 10 min, about 10 g / 10 min to about 50 g / 10 min, about 10 g / 10 min to about 25 g / 10 min, or about 25 g / 10 min to about 50 g / 10 min.

[0027] The crystalline block composite polymers are preferably prepared by a process comprising contacting an addition polymerizable monomer or monomer mixture with a composition comprising at least one addition polymerization catalyst, a cocatalyst and a chain shuttle agent under addition polymerization conditions, the process being characterized by the formation of at least some growing polymer chains under different process conditions in two or more reactors operating under steady-state polymerization conditions or in two or more sections of a reactor operating under plug-flow polymerization conditions. In a preferred embodiment, the block composite may comprise a block polymer fraction having a most probable block length distribution.

[0028] Suitable processes useful for producing crystalline block composites can be found, for example, in U.S. Patent Application Publication No. 2008 / 0269412, published October 30, 2008, which is incorporated herein by reference. In particular, the polymerization is desirably carried out as a continuous polymerization, preferably a continuous solution polymerization, in which the catalyst components, monomers, and optionally solvents, adjuvants, scavengers, and polymerization aids are continuously fed to one or more reactors or compartments, from which the polymer product is continuously removed. As used in this context, within the scope of the terms "continuous" and "continuously" are those processes in which there is intermittent addition of reactants and removal of products at small regular or irregular intervals, such that over time the overall process is substantially continuous. Furthermore, as previously described, the chain shuttle agent(s) may be added at any time during the polymerization, including addition in the first reactor or section, addition at or just before the outlet of the first reactor, or addition between the first reactor or section and the second or any subsequent reactor or section. Due to differences in monomers, temperature, pressure, or other differences in polymerization conditions between at least two of the serially connected reactors or sections, polymer segments having different compositions, such as comonomer content, crystallinity, density, tacticity, regioregularity, or other chemical or physical differences, within the same molecule are formed in the different reactors or sections. The size of each segment or block is determined by the sequential polymer reaction conditions, and preferably forms the most probable polymer size distribution.

[0029] Suitable catalysts and catalyst precursors may include, for example, the metal complexes disclosed in WO2005 / 090426, which is incorporated herein by reference, in particular those disclosed on page 20, line 30 to page 53, line 20. Suitable catalysts are also disclosed in US2006 / 0199930, US2007 / 0167578, US2008 / 0311812, US7,355,089B2, or WO2009 / 012215, which are incorporated herein by reference with respect to catalysts.

[0030] Particularly preferred catalysts are of the formula: [ka] In the formula, R 20 is an aromatic or inertly substituted aromatic group containing 5 to 20 atoms, not counting hydrogen, or a polyvalent derivative thereof; T 3 is a hydrocarbylene or silane group having 1 to 20 atoms, not counting hydrogen, or an inert substituted derivative thereof; M 3 is a Group 4 metal, preferably zirconium or hafnium; G is an anionic, neutral, or dianionic ligand group, preferably a halide, hydrocarbyl, or dihydrocarbylamide group having up to 20 atoms not counting hydrogen; g is a number from 1 to 5 indicating the number of such G groups; and bonds and electron donating interactions are represented by lines and arrows, respectively.

[0031] Preferably, such a complex corresponds to the formula: [ka] In the formula, T 3 is a divalent bridging group having 2 to 20 atoms, not counting hydrogen, preferably a substituted or unsubstituted C3-6 alkylene group, and Ar 2 is independently, in each occurrence, an arylene or alkyl- or aryl-substituted arylene group having 6 to 20 atoms, not counting hydrogen; M 3 is a Group 4 metal, preferably hafnium or zirconium, G is independently at each occurrence an anionic, neutral, or dianionic ligand group, g is a number from 1 to 5 indicating the number of such X groups, and electron donating interactions are represented by arrows.

[0032] Preferred examples of metal complexes of the above formula include the following compounds: [ka]

[0033] In the formula, M 3 is Hf or Zr, and Ar 4 is C6-20 aryl or an inertly substituted derivative thereof, in particular 3,5-di(isopropyl)phenyl, 3,5-di(isobutyl)phenyl, dibenzo-1H-pyrrol-1-yl, or anthracen-5-yl; T 4 independently, at each occurrence, comprises a C3-6 alkylene group, a C3-6 cycloalkylene group, or an inert substituted derivative thereof; R 21 is independently, in each occurrence, hydrogen, halo, hydrocarbyl, trihydrocarbylsilyl, or trihydrocarbylsilylhydrocarbyl having up to 50 atoms not counting hydrogen; G is independently, in each occurrence, a halo or hydrocarbyl or trihydrocarbylsilyl group having up to 20 atoms not counting hydrogen; or two G groups together are a divalent derivative of the foregoing hydrocarbyl or trihydrocarbylsilyl groups.

[0034] Particularly preferred are compounds of the formula: [ka]

[0035] In the formula, Ar4 is 3,5-di(isopropyl)phenyl, 3,5-di(isobutyl)phenyl, dibenzo-1H-pyrrol-1-yl, or anthracen-5-yl; R 21 is hydrogen, halo, or C1-4 alkyl, in particular methyl; T 4 is propane-1,3-diyl or butane-1,4-diyl, and G is chloro, methyl, or benzyl.

[0036] Other suitable metal complexes are of the formula: [ka]

[0037] The aforementioned polyvalent Lewis base complexes are conveniently prepared by standard metallation and ligand exchange procedures involving a source of Group 4 metal and a source of neutral polyfunctional ligand. In addition, the complexes can also be prepared by amide removal and hydrocarbylation processes starting from the corresponding Group 4 metal tetraamide and a hydrocarbylating agent such as trimethylaluminum. Other techniques can be used as well. These complexes are known, inter alia, from the disclosures of U.S. Pat. Nos. 6,320,005, 6,103,657, 6,953,764, and WO 02 / 38628 and WO 03 / 40195.

[0038] Suitable cocatalysts are those disclosed in WO2005 / 090426, in particular those disclosed on page 54, line 1 to page 60, line 12, which are incorporated herein by reference.

[0039] Suitable chain shuttle agents are those disclosed in WO2005 / 090426, which is incorporated herein by reference, in particular those disclosed on page 19, line 21 to page 20, line 12. Particularly preferred chain shuttle agents are dialkyl zinc compounds.

[0040] The crystalline block composite preferably has a Tm of greater than 100° C., preferably greater than 120° C., and more preferably greater than 125° C. Preferably, the Tm is in the range of 100° C. to 250° C., more preferably 120° C. to 220° C., and even more preferably 125° C. to 220° C. Preferably, the MFR of the crystalline block composite is 0.1 to 1000 dg / min, more preferably 0.1 to 50 dg / min, and even more preferably 0.1 to 30 dg / min.

[0041] Preferably, the crystalline block composite has a weight average molecular weight (Mw) of 10,000 to about 2,500,000, preferably 35,000 to about 1,000,000, more preferably 50,000 to about 300,000, preferably 50,000 to about 200,000.

[0042] Preferred suitable CBC resin(s) will have a heat of fusion value, as measured by DSC, of ​​at least about 50 Joules per gram (J / g), more preferably at least about 75 J / g, even more preferably at least about 85 J / g, and most preferably at least about 90 J / g.

[0043] In embodiments, the crystalline block composites may exhibit a refractive index (RI) of 1.49 to 1.52, as determined according to the methods described herein. In some embodiments, the crystalline block composites may exhibit a refractive index (RI) of 1.49 to 1.51.

[0044] Ionomer Reference is now made to the ionomer embodiments of the polymer blends. In embodiments herein, ionomers formed from partially neutralized precursor acid copolymers are disclosed.

[0045] The precursor acid copolymer comprises copolymerized units of ethylene and about 5% to about 30% by weight of copolymerized units of an α,β-ethylenically unsaturated carboxylic acid having 3 to 8 carbon atoms, based on the total weight of the precursor acid copolymer. All individual values ​​and subranges from about 5% to about 30% by weight are included and disclosed herein. For example, in some embodiments, the precursor acid copolymer (a) comprises copolymerized units of ethylene and about 5% to about 25% by weight, about 7% to about 25% by weight, or about 7% to about 22% by weight of copolymerized units of an α,β-ethylenically unsaturated carboxylic acid having 3 to 8 carbon atoms, based on the total weight of the precursor acid copolymer. The comonomer content can be measured using any suitable technique, such as techniques based on nuclear magnetic resonance ("NMR") spectroscopy, for example, by 13C NMR analysis as described in U.S. Patent No. 7,498,282, which is incorporated herein by reference.

[0046] Examples of suitable α,β-unsaturated carboxylic acids having 3 to 8 carbon atoms may include, but are not limited to, acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, monomethylmaleic acid, and combinations of two or more of these acid comonomers. In some embodiments, the α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms includes acrylic acid and methacrylic acid. In other embodiments, the α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms includes acrylic acid.

[0047] The precursor acid copolymer has a melt index I2 of about 10 g / 10 min to about 4,000 g / 10 min. The melt index I2 is determined according to ASTM D1238 at 190° C. and 2.16 kg. All individual values ​​and subranges from 10 g / 10 min to 4,000 g / 10 min are included and disclosed herein. For example, in some embodiments, the precursor acid copolymer can have a melt index I2 of about 10 g / 10 min to about 2,500 g / 10 min, about 10 g / 10 min to about 1,250 g / 10 min, about 25 g / 10 min to about 1,000 g / 10 min, about 25 g / 10 min to about 750 g / 10 min, about 50 g / 10 min to about 500 g / 10 min, or about 100 g / 10 min to about 450 g / 10 min.

[0048] The precursor acid copolymers may be synthesized in a continuous process in which each of the reactive comonomers and the solvent(s), if present, are continuously fed into a stirred reactor together with an initiator. The selection of the initiator is based on the pairing of the expected reactor temperature range of the initiator and the decomposition temperature of the initiator, and the criteria for this selection are well understood in the art. In general, during synthesis by copolymerization of ethylene with the acid comonomer to produce the precursor acid copolymer, the reaction temperature may be maintained at about 120°C to about 300°C, or about 140°C to about 260°C. The pressure in the reactor may be maintained at about 130MPa to about 310MPa, or about 165MPa to 250MPa.

[0049] The reactor may be, for example, an autoclave reactor, such as that described in U.S. Pat. No. 2,897,183, which describes a type of autoclave reactor equipped with a means for vigorous agitation. This patent also describes a continuous process for polymerizing ethylene under a "substantially constant environment." This environment is maintained by keeping certain parameters, such as pressure, temperature, initiator concentration, and the ratio of polymer product to unreacted ethylene, substantially constant during the polymerization reaction. Such conditions may be achieved in any of a variety of continuous stirred tank reactors, including, for example, continuously stirred isothermal reactors and continuously stirred adiabatic reactors.

[0050] The reaction mixture containing the precursor acid copolymer is vigorously stirred and continuously removed from the autoclave.After the reaction mixture leaves the reaction vessel, the resulting precursor acid copolymer product is separated from the volatile unreacted monomer and, if present, the solvent(s) by conventional procedures, such as evaporating the unpolymerized material and the solvent(s) under reduced pressure or at elevated temperature.Non-limiting examples of precursor acid copolymers include NUCREL™ 0403, 0903, or 0910, available from The Dow Chemical Company, Midland, MI.

[0051] In general, to obtain the ionomers described herein, the reactor contents should be maintained during the polymerization reaction under conditions such that a single phase exists substantially throughout the reactor. This can be accomplished by adjusting the reactor temperature, adjusting the reactor pressure, adding a co-solvent, or any combination of these techniques, as described in U.S. Pat. No. 5,028,674. Conventional means can be used to determine whether a single phase is maintained substantially throughout the reactor. For example, Hasch et al., in “High-Pressure Phase Behavior of Mixtures of Poly(Ethylene-co-Methyl Acrylate)with Low-Molecular Weight Hydrocarbons,” Journal of Polymer Science: Part B: Polymer Physics, Vol. 30, 1365-1373 (1992), describe cloud point measurements that can be used to determine the boundary between single-phase and multiphase conditions.

[0052] To obtain ionomers useful in the blends described herein, the precursor acid copolymer is neutralized with a base containing a metal cation such that the acid groups (e.g., carboxylic acid) in the precursor acid copolymer react to form acid salt groups (e.g., carboxylates). In embodiments herein, about 25% to about 65%, or about 30% to about 60%, or about 35% to about 60%, or about 30% to about 55%, or about 35% to about 55% of the acid groups derived from the α,β-ethylenically unsaturated carboxylic acid of the precursor acid copolymer are neutralized. The neutralization level of the acid groups derived from the α,β-ethylenically unsaturated carboxylic acid of the precursor acid copolymer can be calculated based on the amount of basic metal compound added or measured using infrared spectroscopy. The actual neutralization level can be measured using infrared spectroscopy by measuring the IR intensity at 1530-1630 cm. -1 The absorption peaks at 1690-1710 cm are due to the stretching vibration of the carboxylate anion. -1The amount of basic metal compound capable of neutralizing the acidic groups can be provided by adding a stoichiometric amount of basic compound calculated to neutralize the target amount of acid moieties in the acid copolymer. Non-limiting examples of ionomers include SURLYN™ products available from The Dow Chemical Company, Midland, MI.

[0053] Any stable cation and any combination of two or more stable cations are believed to be suitable as counterions for the acid groups of the ionomer. Divalent and monovalent cations such as cations of alkali metals, alkaline earth metals, and some transition metals may be used. In some embodiments, the cation is a divalent cation (e.g., zinc, calcium, or magnesium). In other embodiments, the cation is a monovalent cation (e.g., potassium or sodium). In further embodiments, the acid groups derived from the α,β-ethylenically unsaturated carboxylic acid of the precursor acid copolymer are neutralized with a sodium-ion-containing base. This can provide a sodium ionomer in which the hydrogen atoms of the acid groups of the precursor acid are replaced by sodium cations. To obtain the ionomers used in the present invention, the precursor acid copolymer can be neutralized by any conventional procedure, such as those described in U.S. Pat. Nos. 3,404,134 and 6,518,365.

[0054] The ionomer may have a melt index I2 of 0.1 g / 10 min to 50 g / 10 min according to ASTM D1238 at 190° C., 2.16 kg. All individual values ​​and subranges from 0.1 g / 10 min to 50 g / 10 min are included and disclosed herein. For example, in some embodiments, the ionomer may have a melt index I2 of about 0.1 g / 10 min to about 50 g / 10 min, about 0.1 g / 10 min to about 25 g / 10 min, about 0.1 g / 10 min to about 10 g / 10 min, about 0.1 g / 10 min to about 5 g / 10 min, about 0.1 g / 10 min to about 1 g / 10 min, about 1 g / 10 min to about 50 g / 10 min, about 1 g / 10 min to about 25 g / 10 min, about 1 g The melt index I2 may be from about 10 g / 10 min to about 10 g / 10 min, from about 1 g / 10 min to about 5 g / 10 min, from about 5 g / 10 min to about 50 g / 10 min, from about 5 g / 10 min to about 25 g / 10 min, from about 5 g / 10 min to about 10 g / 10 min, from about 10 g / 10 min to about 50 g / 10 min, from about 10 g / 10 min to about 25 g / 10 min, or from about 25 g / 10 min to about 50 g / 10 min.

[0055] molded product Embodiments of the present disclosure may include molded articles comprising the polymer blends described herein.

[0056] The polymer blends can be injection molded, compression molded, or blow molded into articles for use as cosmetic containers (e.g., caps, bottles, tubs, or thick-walled containers). However, it should be noted that these are merely exemplary implementations of the embodiments described herein. The embodiments are also applicable to other technologies that are subject to similar problems as those described above. For example, the molded articles described herein can be used in other applications such as cell phone covers and cases, and automotive interior components.

[0057] Molded articles may be formed from the blends described herein using processes such as injection molding, blow molding, transfer molding, casting, extrusion, overmolding, compression molding, or cavity molding of the compositions. In some embodiments, the molded article is an injection molded article. In other embodiments, the molded article is a compression molded article.

[0058] In embodiments, the molded article may exhibit an internal haze of 60% or less as determined according to ASTM D1003. In some embodiments, the molded article may exhibit an internal haze of less than 50%, 25%, 20%, or 15% as determined according to ASTM D1003.

[0059] In embodiments, the molded article may exhibit an oven creep of less than 150% elongation after 160 minutes, as determined according to the methods described herein. In some embodiments, the molded article may exhibit an oven creep of less than 140%, 130%, or 120% elongation after 160 minutes.

[0060] In embodiments, the molded article may exhibit a tensile strength of at least 25 MPa as determined according to ISO 527. In some embodiments, the molded article may exhibit a tensile strength of at least 29 MPa or at least 30 MPa.

[0061] In embodiments, the molded article may exhibit a deflection temperature under load (HDT) of greater than 35° C. according to ISO 75 using a load of 0.45 MPa. In some embodiments, the molded article may exhibit a deflection temperature under load (HDT) of greater than 40° C. or 45° C. according to ISO 75 using a load of 0.45 MPa.

[0062] The embodiments described herein may be further illustrated by the following non-limiting examples.

[0063] Test Method Unless otherwise specified, the following test methods are used:

[0064] density Density was determined in accordance with ASTM D792 and is reported in grams per cubic centimeter (ie, g / cc).

[0065] Melt Index Melt index, or I2, was determined according to ASTM D1238 at 190° C., 2.16 kg and is reported in grams per 10 minutes (or g / 10 min).

[0066] Melt Flow Rate Melt flow rate, or MFR, was measured according to ASTM D1238 at 230° C., 2.16 kg and is reported in grams per 10 minutes (or g / 10 min).

[0067] Internal Haze Internal haze is determined according to ASTM D1003 and is reported in %. Samples are compression molded into 6" x 6" x 10 mil (length x width x thickness) films at 210°C by hot pressing and then cooled to room temperature by water cooling for measuring haze.

[0068] Oven Creep Test Film samples 10 mils thick, 3 inches long, and 1 inch wide are prepared by compression molding at 210°C. The film sample is suspended in an oven at a temperature of 85°C and a 30 gram weight is attached to the film sample. The percent dimensional change is calculated by dividing the change in film length by the original film length and is determined at 30 minute intervals over a period of 0 to 240 minutes. A test failure occurs when the film stretches to the point where it touches the bottom of the oven (i.e., a dimensional change of 1200%).

[0069] Heat deflection temperature (HDT) HDT is determined in accordance with ISO 75 using a load of 0.45 MPa and is reported in °C.

[0070] Tensile properties Tensile strength, tensile modulus, and elongation at break are measured according to ISO 527. Type 1A test bars are injection molded for tensile measurements.

[0071] Refractive index The refractive index is measured using a Metricon model 2010 / M prism coupler using a 632.8 nm HeNe laser at ambient temperature and humidity using compression molded plaques (6 mil). The material is molded at a temperature of 190°C to 210°C against a PET (Mylar) sheet backing for a smooth surface. Quench cooling may be used, meaning that the molten plaque is transferred to a platen equipped with a cooling system for rapid cooling.

[0072] Differential Scanning Calorimetry (DSC) Differential scanning calorimetry (DSC) can be used to measure the melting, crystallization, and glass transition behavior of polymers over a wide temperature range. For example, a TA Instruments Q1000 DSC equipped with an RCS (refrigerated cooling system) and an autosampler is used to perform this analysis. A nitrogen purge gas flow rate of 50 ml / min is used during testing. Each sample is melt pressed into a thin film at approximately 175°C, and the molten sample is then air-cooled to room temperature (approximately 25°C). A 3-10 mg, 6 mm diameter specimen is extracted from the cooled polymer, which is weighed, placed into a light (approximately 50 mg) aluminum pan, and crimped shut. Analysis is then performed to determine its thermal properties.

[0073] The thermal behavior of the sample is determined by ramping the sample temperature up and down to create a heat flow vs. temperature profile. First, the sample is rapidly heated to 180°C and held isothermal for 3 minutes to remove its thermal history. Next, the sample is cooled to -40°C at a cooling rate of 10°C / min and held isothermal at -40°C for 3 minutes. The sample is then heated to 180°C at a heating rate of 10°C / min (this is the "second heat" ramp). A cooling curve and a second heating curve are recorded. The cooling curve is analyzed by setting a baseline endpoint from the onset of crystallization to -20°C. The heating curve is analyzed by setting a baseline endpoint from -20°C to the end of melting. The values ​​determined are the extrapolated melting onset, Tm, and the extrapolated crystallization onset, Tc. The heat of fusion (Hf) (also known as enthalpy of fusion) and peak melting temperature are reported from the second heating curve. The peak crystallization temperature is determined from the cooling curve.

[0074] The melting point, Tm, is determined from the DSC heating curve by first drawing a baseline between the onset and end of the melting transition. Then, a tangent line is drawn to the data on the low temperature side of the melting peak. Where this line intersects the baseline is the extrapolated onset of melting (Tm). This is as explained in Bernhard Wunderlich, The Basis of Thermal Analysis, Thermal Characterization of Polymeric Materials 92, 277-278 (Edith A. Turi ed., 2d ed. 1997).

[0075] The crystallization temperature, Tc, is determined from the DSC cooling curve as above, except that a tangent is drawn to the high temperature side of the crystallization peak. Where this tangent intersects the baseline is the extrapolated crystallization onset (Tc).

[0076] Gel Permeation Chromatography (GPC) A high temperature gel permeation chromatography (GPC) system equipped with a Robotic Assistant Deliver (RAD) system is used for sample preparation and sample injection. The concentration detector is an infrared detector (IR-5) from Polymer Char Inc. (Valencia, Spain). Data collection is performed using a Polymer Char DM 100 data acquisition box. The carrier solvent is 1,2,4-trichlorobenzene (TCB). The system is equipped with an online solvent degasser from Agilent. The column compartment is operated at 150°C. The columns are four Mixed A LS 30 cm, 20 micron columns. The solvent is nitrogen purged 1,2,4-trichlorobenzene (TCB) containing approximately 200 ppm of 2,6-di-t-butyl-4-methylphenol (BHT). The flow rate is 1.0 mL / min and the injection volume is 200 μl. A sample concentration of 2 mg / mL is prepared by dissolving the sample in N2-purged and preheated TCB (containing 200 ppm BHT) at 160° C. for 2.5 hours with gentle stirring.

[0077] The GPC column set is calibrated by running 20 narrow molecular weight distribution polystyrene standards. The molecular weights ("MW") of the standards range from 580 g / mol to 8,400,000 g / mol, and the standards are contained in six "cocktail" mixtures. Each standard mixture has at least a 10-fold interval between the individual molecular weights. The equivalent polypropylene molecular weight of each PS standard is calculated by using the following formula, with the reported Mark-Houwink coefficients for polypropylene (Th. G. Scholte, NL J Meijerink, HM Schoffeleers, & A. MG Brands, J. Appl. Polym. Sci., 29, 3763-3782 (1984)) and polystyrene (EPO Tocka, RJ Roe, NY Hellman, & P. ​​M. Muglia, Macromolecules, 4, 507 (1971)):

number

[0078] Logarithmic molecular weight calibrations are generated using fourth order polynomial regression as a function of elution volume. Number average and weight average molecular weights are calculated according to the following formulas:

number

number

[0079] High Temperature Liquid Chromatography (HTLC) The instrumentation of the high temperature liquid chromatography (HTLC) experimental method is carried out according to the published method of D. Lee et al., J. Chromatogr. A 2011, 1218, 7173. Two Shimadzu (Columbia, MD, USA) LC-20AD pumps are used to deliver decane and trichlorobenzene (TCB), respectively. Each pump is connected to a 10:1 fixed flow splitter (part number: 620-PO20-HS, Analytical Scientific Instruments Inc., CA, USA). The splitter has a pressure drop of 1500 psi (10.34 MPa) at 0.1 mL / min in H2O according to the manufacturer. The flow rate of both pumps is set to 0.115 mL / min. After splitting, the fractional flow is 0.01 mL / min for both decane and TCB, determined by weighing the collected solvent over 30 min. The volume of eluate collected is determined by the mass and density of the solvent at room temperature. A small stream is delivered to the HTLC column for separation. The main stream is sent back to the solvent reservoir. A 50 μL mixer (Shimadzu) is connected beyond the splitter to mix the solvents from the Shimadzu pumps. The mixed solvent is then delivered to the injector in the oven of a Waters (Milford, MA, USA) GPCV2000. A Hypercarb™ column (2.1×100 mm, 5 μm particle size) is connected between the injector and a 10-port VICI valve (Houston, TX, USA). The valve is equipped with two 60 μL sample loops. This valve is used to continuously sample the eluate from the HTLC column in the first dimension (D1) to the SEC column in the second dimension (D2). A Waters GPCV2000 pump and a PLgel Rapid™-M column (10×100 mm, 5 μm particle size) are connected to a VICI valve for D2 size exclusion chromatography (SEC). A symmetric configuration is used for the connection, as described in the literature (Y. Brun & P. ​​Foster, J. Sep. Sci. 2010, 33, 3501).A dual-angle light scattering detector (PD2040, Agilent, Santa Clara, Calif., USA) and an IR5 inferential absorbance detector are coupled ahead of the SEC column for concentration, composition, and molecular weight determination.

[0080] Separation for HTLC: Approximately 30 mg is dissolved in 8 mL of decane by gently shaking the vial at 160° C. for 2 hours. The decane contains 400 ppm of BHT (2,6-di-tert-butyl-4-methylphenol) as a radical scavenger. The sample vial is then transferred to a GPCV2000 autosampler for injection. The temperatures of the autosampler, injector, both Hypercarb and PLgel columns, the 10-port VICI valve, and both the LS and IR5 detectors are maintained at 140° C. throughout the entire separation.

[0081] The initial conditions before injection are as follows: the flow rate of the HTLC column is 0.01 mL / min, the solvent composition of the D1 Hypercarb column is 100% decane, the flow rate of the SEC column is 2.51 mL / min at room temperature, the solvent composition in the D2 PLgel column is 100% TCB, and the solvent composition in the D2 SEC column does not change throughout the separation.

[0082] A 311 μL aliquot of the sample solution is injected onto the HTLC column. The injection produces a gradient as described below. 0-10 min, 100% decane / 0% TCB, From 10 to 651 min, the TCB is increased linearly from 0% TCB to 80% TCB.

[0083] The injection also results in the collection of a light scattering signal (LS15) at an angle of 15°, as well as "measure" and "methyl" signals from the IR5 detector (IR measure and IR methyl) using an EZChrom™ chromatography data system (Agilent). The analog signals from the detectors are converted to digital signals via an SS420X analog-to-digital converter. The collection frequency is 10 Hz. The injection also results in the switching of a 10-port VICI valve. The valve switching is controlled by a relay signal from the SS420X converter. The valve is switched every 3 minutes. Chromatograms are collected from 0 to 651 minutes. Each chromatogram is composed of 651 / 3 = 217 SEC chromatograms.

[0084] After the gradient separation, 0.2 mL of TCB and 0.3 mL of decane are used to wash and recalibrate the HTLC column for the next separation. The flow rate for this step is 0.2 mL / min, delivered by a Shimadzu LC-20 AB pump connected to a mixer.

[0085] Data analysis for HTLC: First, a 651-minute raw chromatogram is developed to yield 217 SEC chromatograms. Each chromatogram is in units of 2D elution volume from 0 to 7.53 mL. Integration limits are then set and the SEC chromatogram undergoes spike removal, baseline correction, and smoothing. This process is similar to batch analysis of multiple SEC chromatograms in traditional SEC. The sum of all SEC chromatograms is inspected to ensure that both the left (upper integration limit) and right (lower integration limit) sides of the peak are at the baseline as zero. If not, the integration limits are adjusted and the process is repeated.

[0086] Each SEC chromatogram n from 1 to 217 results in an XY pair in the HTLC chromatogram (n is the fraction number). X n = Elution volume (mL) = D1 flow rate × n × t 切り替え In the formula, t切り替え = 3 minutes is the switching time of a 10-port VICI valve.

number

[0087] The above formula is IR 測定 Using the signal as an example, the resulting HTLC chromatogram shows the concentration of the separated polymer components as a function of elution volume.

[0088] XY pairs of data are IR メチル and LS15 signals. メチル / IR 測定 The ratio of LS15 / IR is used to calculate the calibrated composition. 測定 The ratio of the calibrated weight average molecular weight (M w ) to calculate

[0089] Calibration follows the procedure of Lee et al. HDPE, isotactic polypropylene (iPP), and ethylene / propylene copolymers with propylene contents of 20.0, 28.0, 50.0, 86.6, 92.0, and 95.8 wt.% P were measured using the IR メチル / IR 測定 Used as a standard for calibration. The composition of the standard is determined by NMR. The standard is run by SEC using an IR5 detector. The IR of the obtained standard is メチル / IR 測定 The ratios are plotted as a function of their composition to yield a calibration curve.

[0090] For routine LS15 calibration, a HDPE reference is used. wis previously determined by GPC as 104.2 kg / mol using LS and RI (refractive index) detectors. GPC uses NBS 1475 as the standard in the GPC. This standard has a certified value of 52.0 kg / mol according to NIST. 7-10 mg of the standard is dissolved in 8 mL of decane at 160°C. The solution is injected into the HTLC column in 100% TCB. The polymer is eluted under constant TCB at 100% at 0.01 mL / min. Thus, the polymer peak appears at the void volume of the HTLC column. The calibration constant Ω is calculated by the sum of the LS15 signal (A LS15 ) and I.R. 測定 The sum of the signals (A IR、測定 ) is determined from:

number

[0091] Next, the experimental LS15 / IR 測定 The ratio is M through Ω w is converted to

[0092] C13 nuclear magnetic resonance (NMR) Sample preparation: Samples are prepared by adding 2.7 g of a 50 / 50 mixture of 0.025 M tetrachloroethane-d2 / orthodichlorobenzene in chromium acetylacetonate (relaxation agent) to 0.21 g of sample in a 10 mm NMR tube. The sample is dissolved and homogenized by heating the tube and its contents to 150°C.

[0093] Data Acquisition Parameters: Data are collected using a Bruker 400 MHz spectrometer equipped with a Bruker Dual DUL high temperature cryoprobe. Data are acquired using 320 transients per data file, a pulse repetition delay of 7.3 seconds (6 seconds delay + 1.3 seconds acquisition time), a flip angle of 90 degrees, and inverse gated decoupling at a sample temperature of 125°C. All measurements are performed on non-spinning samples in locked mode. Samples are homogenized immediately prior to insertion into a heated (130°C) NMR sample changer and left in the probe for 15 minutes to thermally equilibrate prior to data acquisition. NMR can be used to determine the total weight percent of ethylene, for example, in terms of the crystalline block composite index or block composite index, discussed below. EXAMPLES

[0094] Example 1 - CBC1 CBC1 is a crystalline block composite comprising 50% by weight of a crystalline ethylene-propylene copolymer (having an ethylene content of 92% by weight) and 50% by weight of isotactic polypropylene, based on the total weight of CBC1.

[0095] CBC1 is prepared using two continuous stirred tank reactors (CSTRs) connected in series. The first reactor is approximately 12 gallons in volume and the second reactor is approximately 26 gallons. Each reactor is hydraulically full and set to operate at steady state conditions. Monomer, solvent, hydrogen, catalyst-1, cocatalyst-1, cocatalyst-2, and CSA-1 are fed to the first reactor according to the process conditions outlined in Table 2. The contents of the first reactor as described in Table 2 flow to the second reactor in series. Additional monomer, solvent, hydrogen, catalyst-1, cocatalyst-1, and optionally cocatalyst-2 are added to the second reactor.

[0096] Catalyst-1 ([[rel-2',2'''-[(1R,2R)-1,2-cyclohexanediylbis(methyleneoxy-κO)]bis[3-(9H-carbazol-9-yl)-5-methyl[1,1'-biphenyl]-2-olato-κO]](2-)]dimethyl-hafnium) and cocatalyst-1, i.e., a methyldi(C)-catalyst of tetrakis(pentafluorophenyl)borate prepared by reacting a long-chain trialkylamine (Armeen™ M2HT available from Akzo-Nobel, Inc.), HCl, and Li[B(CF)4] substantially as disclosed in USP 5,919,983, Example 2. 14~18 The mixture of alkyl)ammonium salts was purchased from Boulder Scientific and used without further purification.

[0097] CSA-1 (diethylzinc, also known as DEZ) and cocatalyst-2 (modified methylalumoxane (MMAO)) were purchased from Akzo Nobel and used without further purification. The solvent for the polymerization reaction is a hydrocarbon mixture (ISOPAR® E) available from ExxonMobil Chemical Company, which is purified through a bed of 13-X molecular sieves prior to use.

[0098] CBC1 is optionally characterized by differential scanning calorimetry (DSC), C13 nuclear magnetic resonance (NMR), gel permeation chromatography (GPC), and high temperature liquid chromatography (HTLC) fractionation. These are described in more detail in U.S. Patent Application Publication Nos. 2011 / 0082257, 2011 / 0082258, and 2011 / 0082249, published April 7, 2011, respectively, which are incorporated by reference herein for descriptions of analytical methods. The measured properties of CBC1 are provided in Table 3. [Table 2] [Table 3]

[0099] Example 2 - Synthesis of CBC2 Crystalline block composite CBC2, containing 70 wt% iPP and 30 wt% EP, was prepared similarly to CBC1 using two continuous stirred tank reactors (CSTRs) connected in series. The reactor conditions are listed in Table 4. Table 5 shows further analytical properties of CBC2. [Table 4] [Table 5]

[0100] Example 3 - Calculated Crystalline Block Composite Index (CBCI) CBCI provides an estimate of the amount of block copolymer in the CBC under the assumption that the ratio of CEB to CAOB in the diblock is the same as the ratio of ethylene to α-olefin in the entire CBC. Based on an understanding of the individual catalyst reaction rates and the polymerization mechanism of the diblock formation by chain shuttle catalysis described herein, this assumption is valid for these statistical olefin block copolymers. This CBCI analysis shows that the amount of PP isolated is less than if the polymer were a simple blend of propylene homopolymer (CAOP in these examples) and polyethylene (CEP in these examples). As a result, the polyethylene fraction contains a significant amount of propylene that would not be present if the polymer were a simple blend of polypropylene and polyethylene. To account for this "excess propylene," a material balance calculation can be performed to estimate the CBCI from the amounts of polypropylene and polyethylene fractions and the weight percent of propylene present in each fraction separated by HTLC. The corresponding CBCI calculations for CBC 1 and CBC2 are provided in Table 6. [Table 6]

[0101] CBCI is measured by first determining the sum of the weight percent of propylene from each component of the polymer, which is the total weight % of propylene / C3 (for the whole polymer) according to Equation 5 below. This mass balance equation can be used to quantify the amount of PP and PE present in a block copolymer. This mass balance equation can also be used to quantify the amount of PP and PE in a binary blend, and can be extended to ternary or n-component blends. In a CBC of 1, the entire amount of PP or PE is contained in the blocks present in the block copolymer and the unbound PP and PE polymers. Weight%C 3全体 =w PP (Weight %C 3 PP )+w PE (Weight %C 3 PE ) (Equation 5) During the ceremony, w PP is the weight fraction of PP in the polymer, and w PE is the weight fraction of PE in the polymer, and wt% C3 PP is the weight percent of propylene in the PP component or block, and wt% C3 PE is the weight percent of propylene in the PE component or block.

[0102] Note that the total weight percent of propylene (C3) is measured from C13 NMR or another compositional measurement that represents the total amount of C3 present in the entire polymer. The weight percent of propylene in the PP blocks (wt% C3 PP) is set to 100 (if applicable) or can be substituted if otherwise known from DSC melting point, NMR measurement, or other compositional prediction. Similarly, the weight percent of propylene in the PE blocks (wt% C3 PE) is set to 100 (if applicable) or can be substituted if otherwise known from DSC melting point, NMR measurement, or other compositional prediction. The weight percent of C3 is shown in Table 6.

[0103] Based on Equation 5, the total weight fraction of PP present in the polymer can be calculated from the mass balance of the total C3 measured in the polymer using Equation 6. Alternatively, it can be estimated from the mass balance of the monomer and comonomer consumption during the polymerization. This generally represents the amount of PP and PE present in the polymer, regardless of whether the PP and PE are present in the unbound components or in the block copolymer. In a conventional blend, the weight fraction of PP and the weight fraction of PE correspond to the individual amounts of PP and PE polymers present. In a CBC, the ratio of the weight fraction of PP to PE is also considered to correspond to the average block ratio between PP and PE present in this statistical block copolymer.

number

[0104] To estimate the amount of block copolymer (diblock) present in the CBC, Equations 7-9 are applied and the amount of isolated PP measured by HTLC analysis is used to determine the amount of polypropylene present in the diblock copolymer. The amount initially isolated or separated in the HTLC analysis represents the "unbound PP" whose composition represents the PP block present in the diblock copolymer. By substituting the total weight % of C3 in the whole polymer on the left side of Equation 7, as well as the weight fraction of PP (isolated by HTLC) and the weight fraction of PE (isolated by HTLC) into the right side of Equation 7, the weight % of C3 in the PE fraction can be calculated using Equations 8 and 9. The PE fraction is described as the fraction separated from the unbound PP and contains the diblock and unbound PE. The composition of the isolated PP is assumed to be the same as the weight percent of propylene in the PP block, as previously described. Weight%C3 全体 =w PP単離 (Weight %C 3 PP)+w PE-画分 (Weight %C 3 PE画分 ) (Formula 7)

number

[0105] The weight percent amount of C3 in the polyethylene fraction by HTLC represents the amount of propylene present in the block copolymer fraction, which is greater than the amount present in the "unbound polyethylene". To account for the "extra" propylene present in the polyethylene fraction, the only way that PP could be present in this fraction is if the PP polymer chains were linked to PE polymer chains (otherwise it would have been isolated with the PP fraction separated by HTLC). Therefore, the PP blocks remain adsorbed in the PE blocks until the PE fraction is separated.

[0106] The amount of PP present in the diblock is calculated using Equation 10.

number

[0107] The amount of diblock present in this PE fraction can be estimated by assuming that the ratio of PP blocks to PE blocks is the same as the overall ratio of PP to PE present in the whole polymer. For example, if the overall ratio of PP to PE in the whole polymer is 1:1, then the ratio of PP to PE in the diblock is also assumed to be 1:1. Therefore, the weight fraction of diblock present in the PE fraction is the weight fraction of PP in the diblock (wPP-diblock) multiplied by 2. Another way to calculate this is to multiply the weight fraction of PP in the diblock (w PP-ジブロック ) divided by the weight fraction of PP in the whole polymer (Equation 6).

[0108] To further estimate the amount of diblock present in the whole polymer, the estimated amount of diblock in the PE fraction is multiplied by the weight fraction of the PE fraction measured from HTLC. To estimate the Crystalline Block Composite Index, the amount of diblock copolymer is determined by Equation 11. To estimate the CBCI, the weight fraction of diblock in the PE fraction calculated using Equation 10 is divided by the total weight fraction of PP (as calculated in Equation 6) and then multiplied by the weight fraction of the PE fraction.

number

[0109] Example 4 - Synthesis of EP1 EP1, which contains 100 wt% ethylene copolymer, was produced using the same catalyst and cocatalyst used to produce CBC2, except that EP1 was produced in a single reactor. For sample EP1, the MFR of the final product was adjusted by manipulating the DEZ flow rate. EP1 was produced in a 12 gallon reactor. [Table 7] [Table 8]

[0110] Example 5 - Synthesis of Ionomer 1 To prepare ionomer 1, a precursor acid copolymer (e.g., a non-neutralized copolymer of ethylene and methacrylic acid) is produced by free radical polymerization in an adiabatic continuously stirred autoclave substantially according to the procedure described in Example 1 of U.S. Pat. No. 5,028,674, with the following exceptions: (1) the reactor conditions can be maintained at a temperature of about 200° C. to about 260° C. and a pressure of 170 MPa to 240 MPa by controlling the ratio of ethylene to methacrylic acid and the initiator flow rate, (2) no propane telogen is fed to the reactor, (3) the total concentration of methanol in the reactor can be maintained at about 2 to 5 mole percent based on the total feed of ethylene, methacrylic acid, methanol, and initiator solutions, and (4) the system is maintained at a steady state where the residence time of materials flowing through the reactor is about 5 seconds to 2 minutes. Tert-butyl peracetate is an initiator that can be utilized as a 50% concentration solution in odorless mineral spirits.

[0111] Example 6 - Preparation of Comparative Blends A-C and Inventive Blend 1 The materials used to produce Comparative Blends A-C and Inventive Blend 1 were Ionomer 1, CBC1, CBC2, and EP1, as described above. The compositions of Comparative Blends A-C and Inventive Blend 1 are provided in Table 9. [Table 9]

[0112] The formulations in Table 9 are made by a melt extrusion process (twin screw extruder, furthermore, barrel temperatures are around 210° C.).

[0113] Example 7 - Analysis of Comparative Blends A-C and Inventive Blend 1 For tensile and HDT testing, the blends were then injection molded into ISO 527 Type 1A test bars. For oven creep testing and internal haze measurements, the formulations were compression molded into 3" x 1" x 10 mil (length x width x thickness) and 6" x 6" x 10 mil films, respectively. The results are set forth below in Tables 10, 11, and 12. [Table 10] [Table 11]

[0114] As shown in Table 10, Inventive Blend 1 exhibited much lower internal haze than Comparative Blend B, which contained only 50 wt% iPP, and Comparative Blend C, which contained only EP copolymer. Because Comparative Blend C had unacceptable internal haze, oven creep testing and deflection temperature under load were not measured. Inventive Blend 1 also exhibited higher deflection temperature under load than Comparative Blends A and B, which contained only ionomer. As shown in Tables 10 and 11, Inventive Blend 1 exhibited a dimensional change of 113% in 150 minutes in oven creep testing, while Comparative Blends A and B both failed. [Table 12]

[0115] As shown in Table 12, Inventive Blend 1 exhibited higher tensile strength, tensile modulus, and elongation at break when compared to Comparatives A-C. Thus, Inventive Blend 1, a crystalline block composite having greater than 50 wt% iPP, enables the resulting blend to exhibit improved thermal, mechanical, and optical properties when compared to blends including block composites having 50 wt% iPP or less.

[0116] Example 8 - Refractive Index Analysis of Ionomer 1, CBC1, CBC2, and EP1 The refractive index of the samples was measured using a Metricon model 2010 / M prism coupler with a 632.8 nm HeNe laser at ambient temperature and humidity using compression molded plaques (6 mil). Comparative ionomer A was molded at 190°C, while CBC1, CBC2, and EP1 were molded at 210°C. The materials were molded against a PET (Mylar) sheet backing for a smooth surface, and quench cooling was used. The refractive index of these materials was tested and is summarized in Table 13. [Table 13]

[0117] As shown in Table 13, Ionomer 1 exhibited a refractive index of 1.4963. For EP1 with 0 wt% iPP, the refractive index was 1.5107. For CBC1 with 50 wt% iPP, the refractive index was 1.5025. For CBC2 with more than 50 wt% iPP (70 wt% iPP), the refractive index was 1.5068. These results indicate that the inclusion of iPP in the samples may result in a refractive index close to that of Ionomer 1. It is believed that a similar refractive index may improve the clarity of the blend.

[0118] The dimensions and values ​​disclosed herein should not be understood to be strictly limited to the exact numerical values ​​recited. Instead, unless otherwise specified, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm."

[0119] All documents cited herein, including any cross-referenced or related patents or applications, if any, and any patent applications or patents to which this application claims priority or benefit, are incorporated herein by reference in their entirety unless expressly excluded or otherwise limited. The citation of any document is not an admission that it is prior art with respect to any embodiment disclosed or claimed herein, or that it teaches, suggests, or discloses any such embodiment, either alone or in combination with any other reference or references. Furthermore, to the extent that a meaning or definition of any term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall govern. The present application also relates to the following aspects: (1) 1. A polymer blend comprising: 1-40 wt. % of a crystalline block composite comprising an EP-iPP diblock polymer, iPP, and EP, wherein iPP is an isotactic polypropylene homopolymer and EP is a copolymer of ethylene and propylene, and the crystalline block composite comprises more than 50 wt. % of iPP; and 60% to 99% by weight of an ionomer formed from a partially neutralized precursor acid copolymer, the precursor acid copolymer comprising: (a) copolymerized units of ethylene; and 5% by weight to 30% by weight, based on the total weight of the precursor acid copolymer, of copolymerized units of an α,β-ethylenically unsaturated carboxylic acid having 3 to 8 carbon atoms, wherein about 25% to about 65% of the acid groups derived from the α,β-ethylenically unsaturated carboxylic acid of the precursor acid copolymer are neutralized. (2) The polymer blend according to (1) above, wherein the ionomer has a melt index I2 (according to ASTM D1238 at 190°C and 2.16 kg) of 0.1 g / 10 min to 50 g / 10 min. (3) 2. The polymer blend of any of the preceding claims, wherein the crystalline block composite has a melt flow rate MFR (according to ASTM D1238 at 230° C., 2.16 kg) of 2 g / 10 min to 50 g / 10 min. (4) 13. The polymer blend of any of the preceding claims, wherein the crystalline block composite comprises greater than 60% by weight of iPP. (5) The polymer blend of any of the preceding, wherein the acid groups are neutralized with one or more of a zinc ion-containing base, a magnesium ion-containing base, and a sodium ion-containing base. (6) The polymer blend according to any of the above, wherein the polymer blend comprises 5 to 15% by weight of the crystalline block composite and 85 to 95% by weight of the ionomer. (7) The polymer blend of any of the preceding, wherein the α,β-ethylenically unsaturated carboxylic acid comprises acrylic acid, methacrylic acid, or a combination thereof. (8) A molded article comprising any of the polymer blends described above. (9) The molded article according to the above, wherein the molded article is an injection molded article or a compression molded article. (10) The molded article according to (8) or (9) above, wherein the molded article exhibits an internal haze of 20% or less. (11) The molded article according to any one of (8) to (10) above, which exhibits an oven creep of elongation of less than 150% after 160 minutes. (12) The molded article according to any one of the above (8) to (11), which exhibits a tensile strength of at least 30 MPa. (13) The molded article according to any one of the above (8) to (12), which exhibits a deflection temperature under load (HDT) of more than 35°C according to ISO 75 using a load of 0.45 MPa. (14) The molded article according to any one of the above (8) to (13), wherein the crystalline block composite exhibits a refractive index (RI) of 1.49 to 1.52.

Claims

1. 1. A polymer blend comprising: 1 to 40 wt. % of a crystalline block composite comprising an EP-iPP diblock polymer, iPP, and EP, wherein the iPP is an isotactic polypropylene homopolymer and the EP is a copolymer of ethylene and propylene, the crystalline block composite comprising more than 50 wt. % to 85 wt. % of iPP; and 60% to 99% by weight of an ionomer formed from a partially neutralized precursor acid copolymer, the precursor acid copolymer comprising: (a) copolymerized units of ethylene; and 5% to 30% by weight, based on the total weight of the precursor acid copolymer, of copolymerized units of an α,β-ethylenically unsaturated carboxylic acid having from 3 to 8 carbon atoms, wherein 25% to 65% of the acid groups of the precursor acid copolymer derived from the α,β-ethylenically unsaturated carboxylic acid are neutralized.

2. 10. The polymer blend of claim 1, wherein the ionomer has a melt index I2 (per ASTM D1238 at 190° C., 2.16 kg) of 0.1 g / 10 min to 50 g / 10 min.

3. 3. The polymer blend of claim 1 or 2, wherein the crystalline block composite has a melt flow rate MFR (according to ASTM D1238 at 230° C., 2.16 kg) of 2 g / 10 min to 50 g / 10 min.

4. 4. The polymer blend of claim 1, wherein the crystalline block composite comprises from greater than 60% to 85% by weight of iPP.

5. 5. The polymer blend of any one of claims 1 to 4, wherein the acid groups are neutralized with one or more of a zinc ion-containing base, a magnesium ion-containing base, and a sodium ion-containing base.

6. 6. The polymer blend of claim 1, wherein the polymer blend comprises 5 to 15 wt. % of the crystalline block composite and 85 to 95 wt. % of the ionomer.

7. 7. The polymer blend of any one of claims 1 to 6, wherein the α,β-ethylenically unsaturated carboxylic acid comprises acrylic acid, methacrylic acid, or a combination thereof.

8. A molded article comprising the polymer blend of any one of claims 1 to 7.

9. The molded article according to claim 8 , wherein the molded article is an injection molded article or a compression molded article.

10. 10. The molded article according to claim 8 or 9, wherein the molded article exhibits an internal haze of 20% or less.

11. The molded article according to any one of claims 8 to 10, wherein the molded article exhibits an oven creep of less than 150% elongation after 160 minutes.

12. The molded article according to any one of claims 8 to 11, wherein the crystalline block composite exhibits a refractive index (RI) of 1.49 to 1.52.

Citation Information

Patent Citations

  • Cap liners, closures and gaskets from multi-block polymers

    JP2008545017A

  • Dynamic vulcanization of compounded compositions, methods of making same, and articles containing same

    JP2018501341A

  • Polyolefin blends containing crystalline block composites for PVC-free wear layers.

    JP2019510115A